Performance-Based Compositive Passive Control Analysis of Multi-Tower Building with Chassis: Optimization of Kelvin-Voigt Dampers - Shangrong Zhang; Yuchen Hu; Chi Zhang; Shihao Li; Ping Tan (Buildings, 2022)
The compositive passive control (CPC) method of “interlayer seismic isolation “plus “shock absorption between adjacent towers” was applied to a multi-tower building (MTB) with a large podium. The interaction between adjacent towers was used to reduce the structural response under seismic action. Based on the Clough–Penzien spectral seismic model, the extended state equation of random response of MTB was derived with the minimum total energy of structural vibration as the optimization control objective. By comparing the seismic scheme and interlayer seismic isolation scheme, the relationship between the control parameters of the connecting control device and the random response of the structure was discussed and analyzed, and the control effect of the composite passive control system under different control schemes was also studied from the perspective of seismic response time history and vibration cumulative energy time history. Through numerical analysis, it was proved that the damping coefficient of the Kelvin-Voigt model has a great influence on the mean square error of total vibration energy while the stiffness coefficient has a poor sensitivity to it. Under the optimization control objective, the connection control device was better arranged at the top of the structure. The control effect can reach 84.64% under the condition of random ground motion as input. The CPC method maintains the advantages of the interlayer seismic isolation scheme and reduces the defect of the response amplification caused by the interlayer isolation, which provides a reference for the follow-up study of the CPC method of MTB.